1999
DOI: 10.1111/1467-9493.00054
|View full text |Cite
|
Sign up to set email alerts
|

The Web‐based Recruitment of Female Foreign Domestic Workers in Asia

Abstract: In the last three decades, there has been an increased “feminisation” of international migration within the Asian region. In part, the increased mobility of women migrant workers within Asia has resulted from the increased bureaucratic regulation of labour migration. This commodification of the migratory process, however, has placed women in significantly more vulnerable positions vis‐´‐vis their male counterparts. Comparatively little research, however, has examined the critical role of private recruitment ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 19 publications
0
16
1
1
Order By: Relevance
“…In wealthier countries such as Hong Kong and Singapore, where 'local' women have been strategically incorporated into development paths through their participation in the formal labour force, a gap in domestic chores has opened up for South-East Asian migrant domestic workers (Huang and Yeoh 1996Law 2001Law , 2002aLaw , 2002bTyner 1999;Yeoh and Huang 1999). Here we find more paradoxes, however, as refusing traditional domestic roles at home may see them reproduced in foreign contexts.…”
Section: Constructing Identitiesmentioning
confidence: 74%
“…In wealthier countries such as Hong Kong and Singapore, where 'local' women have been strategically incorporated into development paths through their participation in the formal labour force, a gap in domestic chores has opened up for South-East Asian migrant domestic workers (Huang and Yeoh 1996Law 2001Law , 2002aLaw , 2002bTyner 1999;Yeoh and Huang 1999). Here we find more paradoxes, however, as refusing traditional domestic roles at home may see them reproduced in foreign contexts.…”
Section: Constructing Identitiesmentioning
confidence: 74%
“…This research is based on a qualitative analysis of web sites maintained by Philippine diasporic organisations. Based on previous research that has identified the functionality and spatiality of web sites (Brunn and Cottle, 1997;Jackson and Purcell, 1997;Warf and Grimes, 1997;Tyner, 1998Tyner, , 1999b, we identified diaspora web sites through the use of Internet search engines such as AltaVista, Excite, Hotbot, Lycos, and Yahoo. Key words guiding our search included Philippine organization, Philippine community, Filipinos/Filipinas.…”
Section: Methodology and Datamentioning
confidence: 99%
“…illustrated in the literature (Brunn and Cottle, 1997;Jackson and Purcell, 1997;Warf and Grimes, 1997;Kitchin, 1998;Tyner, 1998Tyner, , 1999b.…”
mentioning
confidence: 99%
“…Harvey (2000b: 106) concurs, noting that 'insofar as gender, race, and ethnicity [and, I would add, citizenship] are all understood as social constructions rather than essentialist categories, so the effect of their insertion into the circulation of variable capital … has to be seen as a power force reconstructing them in distinctively capitalist ways' (emphasis added). The processes that incorporate foreign migrant domestic workers, for example, into the Hong Kong labour market are exceptionally important (Constable 1997;Tyner 1999). The authorities selectively admit migrant workers to Hong Kong from both mainland China and neighbouring Southeast Asian countries.…”
Section: Sovereignty Under Neoliberalismmentioning
confidence: 99%